Aging and Exocrine Pancreatic Function - Ochi, Koji; Yoshida, Mitsuo; Tanaka, Juntaro; Ishibashi, Tadaaki; Matsumoto, Shuji; Takeda, Masahiko; Kimura, Ikuro; Miyake, Hirofumi; Harada, Hideo (Nihon Rōnen Igakkai zasshi, 1989)
To evaluate the effect of aging on exocrine pancreatic function, fecal chymotrypsin activity (FCA) was measured by a photometric method in 62 healthy controls (20 to 87 years old, average 51.0 years), 42 patients with non-pancreatic diseases (31 to 83 years old, average 56.1 years), 40 controls in an old-age home (63 to 92 years old, average 77.6 years), 20 patients with definite chronic pancreatitis (17 to 72 years old, average 53.5 years) and five patietns with pancreatic cancer (60 to 76 years old, average 65.4 years). Exocrine pancreatic function showed a significant decrease with aging as indicated by: (a) a significant inverse correlationship between aging and FCA in the 62 healthy controls (r=-0.56, p<0.001), in the 42 patients with non-pancreatic diseases (r=-0.59, p<0.001), and also in the 40 controls in an old-age home (r=-0.52, p<0.001); and (b) a significantly lower FCA in the 21 healthy controls aged 65 or more (designated as the B group of healthy controls) than the 41 healthy controls aged less than 65 (designed as the A group of healthy controls). The 40 controls in an old-age home showed significantly lower FCA than the B group of healthy controls. This result was ascribed to the fact that the former group consisted of significantly older subjects than the latter. No significant difference was found in FCA between patients with chronic pancreatitis, those with pancreatic cancer, the B group of healthy controls, and the controls in an old-age home. When m-2SD values (14.5U/g) in the A group of healthy controls was set as the lower normal limit, 60% of patients with pancreatic cancer, 55% of patients with chronic pancreatitis, 52.4% of the B group healthy controls and 62.5% of the controls in an old-age home showed abnormally low levels of FCA. These results suggest that in the elderly, FCA determination is not useful for the diagnosis of pancreatic diseases. However, it is useful to discover moderate to marked exocrine pancreatic dysfunction and to follow up patients with pancreatic diseases.